Evaluation of Dutch guideline for just‐in‐time addition of plerixafor to stem cell mobilization in patients who fail with granulocyte–colony‐stimulating factor. Issue 5 (30th December 2014) - Bilgin, Yavuz M.; Visser, Otto; Beckers, Erik A.M.; te Boome, Liane CJ; Huisman, Cynthia; Ypma, Paula F.; Croockewit, Alexandra J.; Netelenbos, Tanja; Kramer, Ellen PA; de Greef, Georgine E.
<x xml:space="preserve">Abstract</x> Background Plerixafor in combination with granulocyte‐colony‐stimulating factor (G‐CSF) is approved for the use of stem cell collection in patients who fail to mobilize on G‐CSF. In 2009 the Stem Cell Working Party of the Dutch‐Belgian Cooperative Trial group for Hematology Oncology (HOVON) composed a guideline for the use of plerixafor. According to this guideline it is recommended to add plerixafor to G‐CSF in patients with circulating CD34+ cell counts of fewer than 20 × 106/L on 2 consecutive days accompanied by increasing white blood cells. Study Design and Methods In this analysis we evaluated retrospectively the outcome of the use of this guideline in the Netherlands. In total 111 patients received plerixafor with a median one administration (range, one to four administrations). Of these patients 55.8% had non‐Hodgkin lymphoma, 31.5% multiple myeloma, 8.1% Hodgkin lymphoma, and 4.5% nonhematologic malignancies. Results In 63.9% patients sufficient numbers of CD34+ cells were collected. In patients with multiple myeloma more successful mobilizations with plerixafor were observed compared to patients with non‐Hodgkin lymphoma (71.4% vs. 61.3%). In patients with circulating CD34+ cell counts of at least 2.0 × 106/L before administration of plerixafor a successful mobilization was achieved in 76.5%, and in the patients with very low (0‐1 × 106/L) circulating CD34+ cell counts the success rate was 44.2%. Conclusion Application of the HOVON guideline on the just‐in‐time administration of plerixafor is effective for mobilization of hematopoietic stem cells in the majority of patients. Stem cell yield in patients with non‐Hodgkin lymphoma was lower compared to patients with multiple myeloma. Also patients with very low circulating CD34+ cells before addition of plerixafor might benefit from this approach.